CONSTRUCTION TEAM MOVEMENT IN THE CONTEXT OF THE EDUCATIONAL ENVIRONMENT AND LABOR EDUCATION - Semen P. Bashkirov; Yakov Yu. Vasilyev (Высшее образование в России, 2016)
The article differentiates the concept of the educational environment from the concept of organizational culture of an educational institution. The authors consider the role of higher education institutions in formation of the educational environment of the region; describe the individual mechanisms of correction of the educational environment with use of the tools of organizational culture as applied to university public associations on the example of the student construction team movement. Student construction brigade successfully combines the elements of social and economic organization and this enables them to be the connecting link between university and enterprise and also to be a substantial part of a regional educational environment.